2003
DOI: 10.1093/ndt/gfg1033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognostic factors of renal outcome in anti-neutrophil cytoplasmic autoantibody (ANCA)-associated glomerulonephritis in elderly patients

Abstract: The actuarial renal survival rate in elderly patients with ANCA-associated GN was 92% at 1 year and 76% at 3 years. Older age, arterial hypertension, proteinuria and serum creatinine > or =400 micro mol/l related to ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
19
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 11 publications
8
19
1
1
Order By: Relevance
“…Our results extend the observations from the Dutch cohort. Our data are also in agreement with published results from other studies, showing that the renal function at initial presentation is the best predictor for renal function at follow-up (27)(28)(29). However, in contrast to the Dutch study, no significant correlation with the relapse risk was found in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…Our results extend the observations from the Dutch cohort. Our data are also in agreement with published results from other studies, showing that the renal function at initial presentation is the best predictor for renal function at follow-up (27)(28)(29). However, in contrast to the Dutch study, no significant correlation with the relapse risk was found in our cohort.…”
Section: Discussionsupporting
confidence: 92%
“…High creatinine at presentation is a well known risk factor for impaired renal survival (2,12,17,28,29), and we confirmed this in older patients. High creatinine at diagnosis was the only significant predictor of renal survival in multivariable analysis, and treatment with immunosuppressive agents was not significantly associated with renal survival.…”
Section: Discussionsupporting
confidence: 80%
“…This could be because a high ratio of our patients was elderly and dialysis-dependent. As in other recently published series (10,(19)(20)(21) showing that the age of patients with ANCA-associated vasculitis is increasing, the median age of our patients was 72 years and 63% were aged 70 years or older. The 2-year mortality rate of 36% among our patients was similar to the findings of others (9-13) with an older population and severe renal impairment, highlighting the importance of age and renal function for survival.…”
Section: F I G U R E 2 Ka P L a N -Me I E R P L O T I N D I C A T Isupporting
confidence: 83%